Hydration of magnesia cubes: a helium ion microscopy study - Schwaiger, Ruth; Schneider, Johannes; Bourret, Gilles R.; Diwald, Oliver (Beilstein Journal of Nanotechnology, 2016)
Physisorbed water originating from exposure to the ambient can have a strong impact on the structure and chemistry of oxide nanomaterials. The effect can be particularly pronounced when these oxides are in physical contact with a solid substrate such as the ones used for immobilization to perform electron or ion microscopy imaging. We used helium ion microscopy (HIM) and investigated morphological changes of vapor-phase-grown MgO cubes after vacuum annealing and pressing into foils of soft and high purity indium. The indium foils were either used as obtained or, for reference, subjected to vacuum drying. After four days of storage in the vacuum chamber of the microscope and at a base pressure of p < 10−7 mbar, we observed on these cubic particles the attack of residual physisorbed water molecules from the indium substrate. As a result, thin magnesium hydroxide layers spontaneously grew, giving rise to characteristic volume expansion effects, which depended on the size of the particles. Rounding of the originally sharp cube edges leads to a significant loss of the morphological definition specific to the MgO cubes. Comparison of different regions within one sample before and after exposure to liquid water reveals different transformation processes, such as the formation of Mg(OH)2 shells that act as diffusion barriers for MgO dissolution or the evolution of brucite nanosheets organized in characteristic flower-like microstructures. The findings underline the significant metastability of nanomaterials under both ambient and high-vacuum conditions and show the dramatic effect of ubiquitous water films during storage and characterization of oxide nanomaterials.
Keywords: helium ion microscopy; magnesia nanocubes; nanomaterials aging; oxide nanomaterials; surface hydroxylation; thin water films; volume expansion